Non-Equivalence in Translation: Russian-German Diachronic Corpus-Based Dictionaries of Non-Equivalent Units - Alekseyeva, Maria L. (Research in Language, 2021)
This paper explores the essence of lexical units with no direct equivalents in other languages and introduces a bilingual dictionary of a new type. Such a dictionary is built upon a diachronic corpus of parallel translations with due consideration of the principles of present-day lexicography. The suggested diachronic German-Russian glossary of non-equivalent vocabulary – realia – presents the mega-, macro- and microstructure of a diachronic translation dictionary. The glossary is of a holistic character: it can provide information on the ways different realia were translated in various periods and thus reflect the creative role of translation plurality; it can also influence the formation of translating competence, acquisition of translating skills and skills of comparative analysis.